Stimulus-responsive pre-grafted solid polymer electrolyte and all-solid-state battery thereof

The problem of insufficient contact between the electrode and the electrolyte is solved by using stimulus-responsive pregrafted solid polymer electrolyte prepared by mixing iodine-containing graftable polymers with polyethylene oxide in all-solid potassium ion batteries, forming a gap-free The interface and efficient ion transmission network improve the electrochemical stability and ionic conductivity of the battery, achieving stable cycling and high-performance operation at high voltages.

CN119133594APending Publication Date: 2024-12-13XIFENG 2D FUJIAN MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411272650.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In all-solid potassium ion batteries, insufficient contact between the solid electrolyte and the electrode leads to insufficient ion transmission, poor electrochemical cycling performance, and unstable interface under high voltage, resulting in a degradation of battery performance.

Method used

The stimulus-responsive pregrafted solid polymer electrolyte is prepared by mixing iodine-containing graftable polymer with polyethylene oxide and electrolyte salt. The electrolyte undergoes a phase change at high voltage to form a solid permeable phase, fills the electrode gap and Build a void-free ion permeability interface, combine appropriate amounts of I- and I3-ions to avoid dendrite puncture, and improve electrochemical stability and ionic conductivity.

Benefits of technology

It realizes long-term stable cycle of the battery at high voltage, improves electrochemical performance and ion transmission efficiency, ensures high voltage and high performance operation of the battery, especially maintains high Coulomb efficiency at 4.5V.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133594A_ABST
    Figure CN119133594A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of back contact batteries, and particularly relates to a stimuli-responsive pre-grafted solid polymer electrolyte and an all-solid-state battery comprising the stimuli-responsive pre-grafted solid polymer electrolyte. The graft polymer is prepared by mixing and processing with polyethylene oxide and electrolyte salt, and after mixing and processing, the graft polymer is at least partially grafted with polyethylene oxide; the mass of the corresponding graftable polymer is 5%-20% of the mass of polyethylene oxide, the stimuli-responsive pre-grafted solid polymer electrolyte is rich in I <-> and I3 <-> ions, and the total amount of the I <-> and I3 <-> ions is 2%-10% of the mass of the corresponding graftable polymer. The lithium ion battery has excellent high voltage, high performance and stability, and particularly has relatively high electrochemical stability and high ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of back contact batteries, and in particular relates to a stimulus responsive pre-grafted solid polymer electrolyte and an all-solid-state battery thereof. Background Art

[0002] All-solid-state potassium-ion batteries (ASS-PIBs) have attracted extensive attention in energy storage applications due to their low cost, potential high energy density, and good safety. However, achieving high ionic conductivity, high electrochemical voltage, and stable cycling simultaneously remains challenging for all-solid-state electrolytes. Meanwhile, one of the main challenges in achieving stable and extended cycling of ASS-PIBs is the inadequate solid electrolyte (SSEs)-electrode contact interface. Loss of contact between SSEs and electrodes leads to insufficient ion transport and decreased battery performance.

[0003] In addition, interface instability, uneven space charge layer caused by incompatibility, and electrochemical decomposition under high voltage are the main problems of the cathode-electrolyte interface. Therefore, it is very important for batteries to simultaneously improve the compatibility of the cathode-electrolyte contact interface, construct efficient ion transport channels on the cathode side, and solve the stability under high voltage (>4.5V).

[0004] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defect of poor electrochemical cycle performance under high voltage caused by the contact loss problem between electrodes and electrolyte particles in all-solid-state batteries in the prior art, and to provide a stimulus-responsive pre-grafted solid polymer electrolyte and an all-solid-state battery thereof, which can effectively alleviate the contact problem for a long time and are suitable for all-solid-state batteries. The battery has excellent high voltage, high performance and stability, especially high electrochemical stability and high ionic conductivity.

[0006] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a stimulus-responsive pre-grafted solid polymer electrolyte, which is prepared by mixing an iodine-containing graftable polymer or a raw material selected from an iodine compound and a graftable polymer, with polyethylene oxide and an electrolyte salt, and after the mixing process, the corresponding graftable polymer is at least partially grafted with the polyethylene oxide; the mass of the corresponding graftable polymer is 5%-20% of the mass of the polyethylene oxide, and the stimulus-responsive pre-grafted solid polymer electrolyte is rich in I - and I3 - ions, and I - and I3 - The total amount of ions is 2% to 10% of the mass of the corresponding graftable polymer.

[0007] In some preferred embodiments of the present invention, the iodine-containing graftable polymer is selected from polyvinylpyrrolidone-iodine.

[0008] In some preferred embodiments of the present invention, the iodine compound is selected from at least one of elemental iodine, potassium bismuth iodide, sodium triiodide, thallium triiodide, ammonium triiodide, nitrogen triiodide, phosphorus triiodide, antimony triiodide and gallium triiodide, and the graftable polymer is selected from at least one of polyvinyl pyrrolidone, polystyrene, polymethacrylate, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol and poly(vinylidene fluoride-co-hexafluoropropylene).

[0009] In some preferred embodiments of the present invention, the molar ratio of polyethylene oxide to electrolyte salt is 5-20:1.

[0010] In some preferred embodiments of the present invention, the stimulus-responsive pre-grafted solid polymer electrolyte undergoes a phase change to generate a solid permeation phase when stimulated by a voltage greater than 3V.

[0011] In some preferred embodiments of the present invention, the mixing process includes: dissolving each material in an organic solvent, stirring at 50-60° C. for 10-12 hours; then casting, drying, and finally evaporating to remove the residual organic solvent.

[0012] In some preferred embodiments of the present invention, the drying is natural drying in a low dew point environment of 30-50°C; and / or, the evaporation conditions include: in a vacuum environment, a treatment temperature of 30-50°C, and a treatment time of 12-24h.

[0013] In a second aspect, the present invention provides an all-solid-state battery, comprising a positive electrode, a negative electrode, and also comprising the stimulus-responsive pre-grafted solid polymer electrolyte described in the first aspect disposed between the positive electrode and the negative electrode.

[0014] In some preferred embodiments of the present invention, during the charge and discharge process of the all-solid-state battery, the stimulus-responsive pre-grafted solid polymer electrolyte undergoes a phase change to produce a solid permeation phase, resulting in direct contact between the solid permeation phase and the adjacent electrode to form a void-free interface.

[0015] In some preferred embodiments of the present invention, the area of ​​the stimulus responsive pre-grafted solid polymer electrolyte is greater than the positive electrode area and greater than the negative electrode area; and / or, the area of ​​the stimulus responsive pre-grafted solid polymer electrolyte is 1.2 times to 1.5 times the area of ​​the positive electrode or the negative electrode.

[0016] In some preferred embodiments of the present invention, the thickness of the stimulus-responsive pre-grafted solid polymer electrolyte is controlled to be 100 μm-200 μm, and the positive electrode loading is 1.2-1.5 mg / cm 2When the negative electrode is a metal negative electrode, the thickness of the metal negative electrode is 200-300 μm, and when the negative electrode is a graphite negative electrode, the loading amount of the graphite negative electrode is 1.5-2 mg / cm 2 .

[0017] In some preferred embodiments of the present invention, the all-solid-state battery comprises any one of an all-solid-state ion battery and an all-solid-state metal battery, the all-solid-state ion battery includes at least one of a lithium ion battery, a sodium ion battery, and a potassium ion battery, and the all-solid-state metal battery includes at least one of a lithium metal battery, a sodium metal battery, and a potassium metal battery.

[0018] Beneficial effects:

[0019] The present invention adopts the above technical scheme, especially adopts an iodine-containing graftable polymer or a raw material selected from an iodine compound and a graftable polymer, and mixes and processes with polyethylene oxide and an electrolyte salt to prepare a stimulus-responsive pre-grafted solid polymer electrolyte (abbreviated as PGSPE). Under the stimulation of charge / discharge voltage, the PGSPE will undergo an in-situ phase change to produce a solid permeable phase (abbreviated as SPP), and in-situ construct a gap-free ion permeation interface between the PGSPE and the electrode and an effective permeable ion transport network inside the electrode (its three-dimensional structure is as shown in FIG. 1 ) during the cycle process. Figure 1 As shown in the rightmost figure in the figure, during the charge and discharge process, the solid infiltration phase fills the gaps at the interface and penetrates the electrode, forming a strong bond with the electrode. - and I3 - Ions can effectively prevent dendrites from puncturing the permeation phase polymer, thereby effectively alleviating the contact problem for a long time, and it is suitable for all-solid-state batteries. The battery has excellent high voltage, high performance and stability, especially high electrochemical stability and high ionic conductivity, such as stable cycling at 4.5V. In one embodiment, when used in all-solid-state potassium ion batteries, high coulombic efficiency is maintained in 250 cycles at a high operating voltage of 4.5V. And the high performance and stable operation of the all-solid-state potassium ion soft-pack battery based on PGSPE were verified by the scale-up manufacturing test of the soft-pack battery.

[0020] In the present invention, the corresponding graftable polymer and polyethylene oxide form a grafted polymer, the electrochemical stability of PGSPE is improved, and a voltage stimulation response is generated under the action of a voltage greater than 3V, and the corresponding graftable polymer is obtained by depolymerization and separation, and the permeation phase polymer is formed to penetrate into the electrode-solid electrolyte interface and the interior of the electrode material, filling the gap between the interface and the electrode material; at the same time, I3 -Ions react with potassium, sodium, lithium and other dendrites to form iodized interfaces, preventing dendrites from piercing the permeating phase polymer, effectively ensuring that there is always a gapless ion permeation interface between PGSPE and the electrode, and the metal ions in the electrolyte salt can be complexed with the ether oxygen on the permeating phase polymer to achieve the transmission of metal ions in PEO, providing a reliable transmission channel for metal ions, which is beneficial to the transmission of metal ions and thus improves the electrochemical performance of the battery. Under the same conditions, if I3 - Ions will exist in dendrites and pierce the percolating phase polymer, destroying the void-free ion permeation interface.

[0021] Among them, the present invention adopts the corresponding graftable polymer in an appropriate amount ratio and the I - and I3 - ions, which are beneficial to improving ionic conductivity and inhibiting dendrites, thereby balancing the comprehensive effect of forming a sufficient amount of permeating phase polymer and effectively avoiding dendrites piercing the permeating phase polymer, thereby improving electrochemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the preparation examples of the present invention, the drawings required for use in the preparation examples are briefly introduced below. It should be understood that the following drawings only show certain preparation examples of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 From left to right in the figure are: a schematic diagram of the three-dimensional structure of a conventional all-solid-state battery having voids at the cathode-solid electrolyte (SSE) interface and loss of contact between electrode particles and SSE during cycling, a schematic diagram of the three-dimensional structure of using the stimulus responsive pre-grafted solid polymer electrolyte (PGSPE) of the present invention to fill electrode voids, and a schematic diagram of the three-dimensional structure of using the stimulus responsive pre-grafted solid polymer electrolyte (PGSPE) of the present invention to in situ generate a solid permeating phase to fill the voids to achieve void-free interface contact.

[0024] Figure 2 is a cross-sectional SEM image of the solid infiltrated phase cathode.

[0025] Figure 3 is the ionic conductivity of PEO-KFSI and PGSPE electrolytes containing different mass fractions of PVPI (wt% = 5, 10, 15 and 20).

[0026] Figure 4 It is the curve of ionic conductivity of PEO-KFSI and PGSPE (PVPI is 10wt% of the mass of PEO) changing with temperature.

[0027] Figure 5 CV curves of PEO-KFSI and PGSPE (PVPI is 10 wt% of the mass of PEO) in PB / potassium button cells, respectively.

[0028] Figure 6 The graphs are the cycle performance curves of PEO-KFSI and the PGSPE of the present invention used in PB / potassium button batteries respectively.

[0029] Figure 7 It is the charge and discharge curve of the all-solid-state potassium metal battery using PEO-KFSI and the PGSPE of the present invention.

[0030] Figure 8 The figure shows the cycle performance data and corresponding charge-discharge curve of a button battery using PEO-KFSI (original SPE, cut-off voltage of 4.2V) electrolyte; (a) is the cycle performance data diagram, and (b) is the charge-discharge curve.

[0031] Fig. 9 The figures are the cycle performance data diagram and the corresponding charge-discharge curve of the button battery using the PGSPE (cut-off voltage is 4.5V) electrolyte of the present invention; wherein (a) is the cycle performance data diagram, and (b) is the charge-discharge curve.

[0032] Fig.10 This is a data chart of the cycle performance of the PGSPE of the present invention for solid-state K metal soft-pack batteries.

[0033] Fig.11 These are verification diagrams of the thermal runaway behavior of liquid soft-pack batteries and solid-state soft-pack batteries using PGSPE; among them, (a) is the corresponding verification diagram of the liquid soft-pack battery, and (b) is the corresponding verification diagram of the solid-state soft-pack battery using PGSPE.

[0034] Fig.12 The potassium metal battery using PEO-KFSI and PGSPE of the present invention is - and I3 - SEM images of the reaction between ions and potassium dendrites to inhibit dendrites and schematic diagrams of inhibiting dendrites; wherein, (a) is a SEM image of the surface morphology of potassium metal in a potassium metal battery using PEO-KFSI, (b) is a SEM image of the surface morphology of potassium metal in a potassium metal battery using the PGSPE of the present invention, and (c) is a schematic diagram of the principle of inhibiting dendrites in a potassium metal battery using the PGSPE of the present invention. DETAILED DESCRIPTION

[0035] In the present invention, unless otherwise specified, directional words such as "upper, lower, left, right" are generally understood in conjunction with the directions shown in the drawings and actual applications.

[0036] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0037] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all mean that they can be included or not (or can be included or not).

[0039] In a first aspect, the present invention provides a stimulus-responsive pre-grafted solid polymer electrolyte, which is prepared by mixing an iodine-containing graftable polymer or a raw material selected from an iodine compound and a graftable polymer, with polyethylene oxide and an electrolyte salt, wherein after the mixing process, the corresponding graftable polymer is at least partially grafted with the polyethylene oxide; the mass of the corresponding graftable polymer is 5%-20% of the mass of the polyethylene oxide, and the stimulus-responsive pre-grafted solid polymer electrolyte is rich in I - and I3 - ions, and I - and I3 - The total amount of ions is 2% to 10% of the mass of the corresponding graftable polymer.

[0040] Conventional all-solid-state batteries have voids at the cathode-solid electrolyte (SSE) interface and lose contact between electrode particles and SSE during cycling, making ion migration difficult or impossible. Figure 1As shown in the leftmost figure. The stimuli-responsive pre-grafted solid polymer electrolyte (PGSPE) of the present invention generates a solid permeation phase in situ to fill the gaps, achieving a gap-free interface contact, thereby constructing a permeable positive electrode. The three-dimensional structure before and after the phase change is shown in FIG. Figure 1 The cross-sectional SEM image of the permeable positive electrode in one embodiment is shown in the middle figure and the rightmost figure. Figure 2 As shown. Figure 1 and Figure 2 It can be seen from the figure that the stimuli-responsive pre-grafted solid polymer electrolyte (PGSPE) of the present invention generates a solid infiltration phase in situ to fill the gaps, achieving a gap-free interface contact, and solving the problem of contact loss between the traditional electrode and the electrolyte particles; at the same time, I3 - Ions react with potassium, sodium, lithium and other dendrites to form iodine interfaces, preventing dendrites from piercing the permeating phase polymer (such as Fig.12 As shown), it effectively ensures that there is always a gap-free ion permeation interface between PGSPE and the electrode. - and I3 - ions, which is beneficial to improve ionic conductivity and inhibit dendrites.

[0041] The graftable polymer described in the present invention refers to a polymer that can be grafted with PEO (ie, polyethylene oxide).

[0042] It is understood that when the raw material includes an iodine-containing graftable polymer, the corresponding graftable polymer is an iodine-containing graftable polymer; when the raw material includes an iodine compound and a graftable polymer, the corresponding graftable polymer is a graftable polymer. The mass of the corresponding graftable polymer is 5%-20% of the mass of polyethylene oxide, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc. and the range between any two point values, for example, it can be preferably 5%-15%. The mass ratio of the corresponding graftable polymer to polyethylene oxide is in an appropriate range, which is conducive to improving ionic conductivity.

[0043] In the present invention, the polyvinyl pyrrolidone iodine or iodine compound will undergo iodine dissociation during the mixing process to form I - and I3 - Ions are fixed in the stimulus-responsive pre-grafted solid polymer electrolyte. In some preferred embodiments of the present invention, the stimulus-responsive pre-grafted solid polymer electrolyte has - and I3 - The mass ratio of ions is 1:1. - and I3 -Stimuli-responsive pre-grafting of ions into solid polymer electrolytes is beneficial for improving ionic conductivity and suppressing dendrites.

[0044] I - and I3 - The total amount of ions is 2%-10% of the mass of the graftable polymer, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. and the range between any two points.

[0045] In some preferred embodiments of the present invention, the iodine-containing graftable polymer is selected from polyvinyl pyrrolidone iodine. Compared with the method of iodine compounds and polyvinyl pyrrolidone, the use of polyvinyl pyrrolidone iodine can more easily and quickly form a permeation phase and effectively inhibit dendrites.

[0046] In some preferred embodiments of the present invention, the iodine compound is selected from at least one of elemental iodine, potassium bismuth iodide, sodium triiodide, thallium triiodide, ammonium triiodide, nitrogen triiodide, phosphorus triiodide, antimony triiodide and gallium triiodide.

[0047] Preferably, the graftable polymer is at least one selected from polyvinyl pyrrolidone, polystyrene, polymethacrylate, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, poly(vinylidene fluoride-co-hexafluoropropylene).

[0048] In some preferred embodiments of the present invention, the molar ratio of polyethylene oxide to electrolyte salt is 5-20: 1, for example, specifically 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1. According to the preferred embodiment of the present invention, polyethylene oxide and electrolyte salt are used in a suitable molar ratio, which is more conducive to improving ionic conductivity.

[0049] The feasible range of the electrolyte salt in the present invention is relatively wide, and it can be a salt used for electrolytes of various batteries in the prior art, for example, it can be at least one of sulfonyl imide salts, phosphates, chlorates, etc. The metal elements in any electrolyte salt can be independently selected from at least one of potassium, sodium, lithium, zinc, magnesium, and aluminum, and all can be used in the present invention. More preferably, the electrolyte salt is selected from at least one of bisfluorosulfonyl imide salts, hexafluorophosphates, bistrifluoromethanesulfonyl imide salts, and perchlorates.

[0050] In some preferred embodiments of the present invention, the stimuli-responsive pre-grafted solid polymer electrolyte undergoes a phase change to produce a solid permeation phase when stimulated by a voltage greater than 3 V. When stimulated by a voltage greater than 3 V, the stimuli-responsive pre-grafted solid polymer electrolyte undergoes a phase change in situ, so that the SSE-electrode interface is connected to the ion transport channel to form a void-free SSE-electrode interface.

[0051] In some preferred embodiments of the present invention, the mixing process includes: dissolving each material in an organic solvent, stirring at 50-60°C for 10-12 hours; then casting, drying, and finally evaporating to remove the residual organic solvent. The use of this suitable mixing process, combined with the raw materials of the present invention, is more conducive to forming a uniform and dense solid polymer electrolyte.

[0052] The organic solvent can be used as long as it can dissolve various materials, for example, it can be at least one of acetonitrile, anisole, chloroform, dichloroethane, dimethylformamide, etc.

[0053] In some preferred embodiments of the present invention, the drying is natural drying in a low dew point environment of 30-50°C.

[0054] In some preferred embodiments of the present invention, the evaporation conditions include: in a vacuum environment, a treatment temperature of 30-50° C., and a treatment time of 12-24 h.

[0055] In a second aspect, the present invention provides an all-solid-state battery, comprising a positive electrode, a negative electrode, and the stimulus-responsive pre-grafted solid polymer electrolyte of the first aspect disposed between the positive electrode and the negative electrode. The stimulus-responsive pre-grafted solid polymer electrolyte of the present invention is applicable to various all-solid-state batteries, and the effects of the present invention can be obtained.

[0056] In some preferred embodiments of the present invention, during the charge and discharge process of the all-solid-state battery, the stimulus-responsive pre-grafted solid polymer electrolyte undergoes a phase change to produce a solid permeation phase, resulting in direct contact between the solid permeation phase and the adjacent electrode to form a void-free interface.

[0057] In some preferred embodiments of the present invention, the area of ​​the stimulus-responsive pre-grafted solid polymer electrolyte is greater than the area of ​​the positive electrode and greater than the area of ​​the negative electrode; and / or, the area of ​​the stimulus-responsive pre-grafted solid polymer electrolyte is 1.2 to 1.5 times the area of ​​the positive electrode or the negative electrode. The use of the stimulus-responsive pre-grafted solid polymer electrolyte of the present invention with a preferred suitable area relative to the positive electrode or the negative electrode is more conducive to preventing short circuits.

[0058] In some preferred embodiments of the present invention, the thickness of the stimulus-responsive pre-grafted solid polymer electrolyte is controlled to be 100 μm-200 μm, and the positive electrode loading is 1.2-1.5 mg / cm2 When the negative electrode is a metal negative electrode, the thickness of the metal negative electrode is 200-300 μm, and when the negative electrode is a graphite negative electrode, the loading amount of the graphite negative electrode is 1.5-2 mg / cm 2 The use of a stimulus-responsive pre-grafted solid polymer electrolyte of appropriate thickness, combined with a positive electrode and a negative electrode of appropriate loading amount, is more conducive to ion transport and improves interface stability.

[0059] The positive electrode and the negative electrode described in the present invention can both be corresponding electrode compositions for batteries, and can both be used in the present invention. For example, the positive electrode can include a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder. The positive electrode active material can be, for example, a Prussian blue positive electrode, lithium iron phosphate, lithium cobalt oxide, NCM ternary material, etc. Common lithium sodium potassium positive electrode materials all have a solid permeation phase phenomenon; the negative electrode can include, for example, a negative electrode material, a negative electrode conductive agent, and a negative electrode binder. The negative electrode material can be, for example, a graphite negative electrode, a potassium negative electrode, or a potassium-decomposed graphite negative electrode; the optional types and amounts of each corresponding conductive agent and binder, as well as the preparation methods thereof and each corresponding electrode active material can refer to the scope of the prior art, respectively, and can all be used in the present invention. In one specific embodiment, the Prussian blue cathode material is prepared by the following preparation method: FeCl3 solution is added dropwise to K4Fe(CN)6·3H2O solution, and high-speed stirring is maintained throughout the dropping process, and the speed of high-speed stirring is 500-1000rpm. After the dropping is completed, stirring is continued for 2-12 hours, and then aged for 12-24 hours, and then the precipitate is separated, and the precipitate is vacuum dried at 60-80°C for 12-24 hours, and then ground. The molar ratio of K4Fe(CN)6·3H2O and FeCl3 can be determined according to needs, for example, it can be 1:2-3.

[0060] Furthermore, the preparation of the potassium-containing graphite negative electrode may, for example, include: using conventional KFSI / EC / DEC electrolyte as a pre-potassium solution, spraying the solution evenly on the graphite negative electrode through a spray system, and then spreading fresh potassium foil on the surface of the graphite negative electrode, standing for 4 hours to complete the pre-potassium process, and finally transferring the potassium-containing graphite negative electrode to a drying system to remove the residual solution.

[0061] In some preferred embodiments of the present invention, the all-solid-state battery comprises any one of an all-solid-state ion battery and an all-solid-state metal battery, the all-solid-state ion battery comprises at least one of a lithium ion battery, a sodium ion battery, and a potassium ion battery, and the all-solid-state metal battery comprises at least one of a lithium metal battery, a sodium metal battery, and a potassium metal battery. The specifications of each battery may be, for example, a button battery and a soft pack battery.

[0062] The following detailed description of the examples of the present invention is illustrative and is only used to explain the present invention, and should not be construed as limiting the present invention. Among them, the positive electrode and potassium negative electrode of the button battery are circular test pieces with diameters of 14 mm and 16 mm, respectively. The specifications of the positive plate and potassium negative plate of the soft-pack battery are 40×50 mm and 40×50 mm, respectively. The area of ​​the stimulus-responsive pre-grafted solid polymer electrolyte (PGSPE) is 1.3 times the area of ​​the corresponding positive electrode and 1.3 times the area of ​​the corresponding negative electrode. Its thickness is controlled at 130 μm, and the positive electrode loading is 1.4 mg / cm 2 .

[0063] In the subsequent examples, the electrochemical properties of the electrolyte were tested using the CHI600E electrochemical measurement system and charge-discharge system. All tests were performed at a constant temperature (50°C). The main electrochemical properties tested included the ionic conductivity of the electrolyte, cyclic voltammetry curves, potassium symmetric battery cycle performance, and charge-discharge cycle performance.

[0064] Preparation Example 1

[0065] Preparation of electrolyte:

[0066] The electrolyte was prepared in a glove box filled with argon. A certain proportion of PEO (average molecular weight Mv 600000, powder) and KFSI (concentration 99.0wt%) were weighed and dissolved in 15mL acetonitrile (ACN) solution, and stirred at 60°C for 24h to obtain a PEO-KFSI solution. The molar ratio of PEO to KFSI was 10:1.

[0067] The PEO-KFSI-PVPI solution was prepared by the same method and was obtained by adding different mass fractions of PVPI (PVPI was wt% of PEO mass = 5, 10, 15 and 20) to the PEO-KFSI solution.

[0068] Next, the PEO-KFSI and PEO-KFSI-PVPI solutions were cast on a polytetrafluoroethylene (PTFE) mold in a glove box with a spatula and left overnight to dry naturally. Finally, the residual solvent was evaporated in a vacuum oven (60°C, 12h) to obtain PEO-KFSI solid polymer electrolyte (i.e., traditional solid electrolyte) and stimuli-responsive pre-grafted solid polymer electrolyte (PGSPE). The stimuli-responsive pre-grafted solid polymer electrolyte is rich in I - and I3 - Ion, I - and I3 - The mass ratio of ions is 1:1.

[0069] The ionic conductivity of each solid electrolyte obtained above was tested at a desired temperature. Specifically, the ionic conductivity change curves of PEO-KFSI and PGSPE electrolytes containing different mass fractions of PVPI (wt% = 5, 10, 15 and 20) are as follows: Figure 3 As shown, the ionic conductivity of PEO-KFSI and PGSPE (PVPI is 10wt% of PEO mass) varies with temperature as shown Figure 4 shown.

[0070] pass Figure 3 The results show that the present invention can effectively improve the ionic conductivity of pure PEO-KFSI electrolyte through the stimulus responsive pre-grafted solid polymer electrolyte (PGSPE), has high ionic conductivity, is conducive to achieving stable ion transport, and ensures the normal operation of the battery; among them, the example in which PGSPE contains 10wt% PVPI shows the best ionic conductivity. Figure 4 The temperature dependence of the ionic conductivity of PEO-KFSI and PGSPE showed that PGSPE had a higher ionic conductivity.

[0071] Application Examples

[0072] Taking PEO-KFSI and PGSPE (PVPI is 10 wt% of the mass of PEO) in Preparation Example 1 as an example, the following applications were carried out and performance tests were performed.

[0073] 1. Preparation of Prussian blue positive electrode material:

[0074] First, take 160mL K4Fe(CN)6·3H2O (purity 99wt%) and 40mL FeCl3 (purity 99.9wt%) (molar ratio of the two is 1:2), then slowly add the FeCl3 solution to the K4Fe(CN)6 solution through a separatory funnel, keep high-speed stirring at 800rpm, continue stirring for 2h, and then age for 24h. The precipitate is centrifuged three times with deionized water and anhydrous ethanol, and vacuum dried at 80℃ for 24h. Finally, the positive electrode material powder is ground to obtain the Prussian blue active substance, which is stored in a glove box.

[0075] Preparation of positive electrode. The Prussian blue active material, conductive agent Super P, and binder polyvinylidene fluoride obtained above were vacuum dried, weighed at a weight ratio of 6:2:2, mixed with N-methylpyrrolidone solvent, and ball milled for 6 hours to obtain a uniform PB positive electrode mixture slurry. Then, the slurry was coated on the current collector carbon-coated aluminum foil by a coater and dried at 120°C. Finally, the positive electrode was dried in a vacuum oven at 80°C for 24 hours and placed in a glove box for use (the packing density of the PB positive electrode is 1.2-1.5 mg·cm -2 ).

[0076] 2. Application of potassium metal battery:

[0077] PEO-KFSI and PGSPE (PVPI is 10wt% of PEO mass) were used in the potassium button cells with the above-obtained PB positive electrode and potassium metal negative electrode, respectively, and their CV curves were measured as follows: Figure 5 Its cycle performance is shown in Figure 6 The charge and discharge curves are shown as Figure 7 shown.

[0078] Figure 5 It can be seen that the PEO-KFSI electrolyte cannot achieve normal ion transport; on the contrary, PGSPE exhibits complete redox peaks, indicating that it is able to migrate ions normally and matches well with PB.

[0079] at the same time, Figure 6 It is shown that batteries using PGSPE exhibit good reversible plating / stripping of potassium metal, maintaining stable cycling and low polarization; in contrast, potassium metal batteries using PEO-KFSI electrolytes have extremely short life, severe polarization, and may even short circuit early or fail to cycle during the cycling process.

[0080] As can be seen from the above, compared with pure PEO-KFSI, the PGSPE of the present invention has higher ionic conductivity and stability to potassium metal, which enables it to be used in potassium ion batteries and potassium metal batteries. Maintaining long-term stability when operating at high voltage is crucial to battery stability. The battery performance of the battery using PEO-KFSI electrolyte is as follows Figure 8 As shown, it is shown that the battery using PEO-KFSI electrolyte exhibits significant and sustained voltage oscillations and high polarization is observed.

[0081] Figure 7 It shows that the continuous decomposition of PEO-KFSI leads to overcharge and micro-short circuit failure (cut-off voltage is only 4.2V); the battery containing PGSPE of the present invention shows a perfect voltage distribution curve (cut-off voltage is 4.2V, 4.5V and 4.6V), and can still maintain low polarization at high voltage. On the basis of this high voltage stability, the battery of PGSPE of the present invention verifies the cycle recovery performance of PGSPE by setting different rates (charging cut-off voltage 4.5V).

[0082] Moreover, the battery capacity of the PGSPE electrolyte of the present invention was tested at different rates. The results are shown in Table 1. It exhibits excellent rate performance and high capacity when cycled at 0.05C, 0.1C, 0.2C, 0.5C and 1C (2.4-4.5V), providing high specific capacities of 143.6, 126.5, 115.7, 101.5 and 84.5 mAh g-1, respectively, and has good rate cycle recovery.

[0083] Table 1

[0084] Magnification / c 0.05 0.1 0.2 0.5 1 0.5 0.2 0.1 0.05 <![CDATA[Specific capacity / mAh g -1 > 143.6 126.5 115.7 101.5 84.5 99.9 115.9 128.3 143.5

[0085] The battery cycle performance curves of the conventional battery using PEO-KFSI and the PB / potassium metal battery using PGSPE of the present invention are shown as follows: Figure 8 , Fig. 9 As shown in the figure, it can be seen that the present invention can show stable cycling ability at a high charging cut-off voltage of 4.5V, and the initial capacity is as high as 113.28mAh·g -1 ; And the present invention can still maintain a stable high Coulombic efficiency (capacity retention rate is 84%) after 200 cycles at 0.2C.

[0086] 3. Use PB positive electrode and K metal to assemble a soft pack battery with PGSPE (2.5-4.5V) and test its cycle performance. The results are as follows Fig.10 As shown, it can be seen that after 120 cycles at 0.5C, the capacity decay is not obvious and the Coulombic efficiency remains high and stable.

[0087] Moreover, the safety verification of liquid soft-pack batteries and solid-state soft-pack batteries using PGSPE was tested, and the results were as follows: Fig.11 As shown ( Fig.11 The corresponding temperature in the figure represents the thermal runaway temperature of the corresponding battery in the air). It can be seen that the soft-pack battery using organic liquid electrolyte has severe thermal runaway due to continuous exposure to air, and violent combustion occurs without direct contact with the ignition source (see Fig.11 ); however, the solid-state soft-pack battery using PGSPE did not show obvious thermal runaway behavior when continuously exposed to air (see Fig.11 Due to the immobility and non-volatility of the solid electrolyte, the battery will not burn without direct contact with an ignition source.

[0088] The stimuli-responsive pre-grafted solid polymer electrolyte (PGSPE) of the present invention generates a solid permeation phase in situ to fill the gaps and achieve a void-free interface contact, thereby constructing a permeable positive electrode, and its three-dimensional structure before and after the phase change is as follows: Figure 1The cross-sectional SEM images of the corresponding permeable positive electrode are shown in the middle and rightmost figures. Figure 2 As shown in the figure, it can be seen that the stimulus-responsive pre-grafted solid polymer electrolyte (PGSPE) of the present invention generates a solid infiltration phase in situ to fill the gaps, achieves interfacial contact without gaps, and solves the problem of contact loss between traditional electrodes and electrolyte particles.

[0089] Preparation Example 2

[0090] PGSPE was prepared by referring to the method of the PEO-KFSI-PVPI solution in Preparation Example 1 (PVPI was 10 wt % of the mass of PEO), except that the mass of PVPI was 15% of the mass of polyethylene oxide.

[0091] Preparation Example 3

[0092] PGSPE was prepared by referring to the method of PEO-KFSI-PVPI solution (PVPI is 10wt% of PEO mass) in Preparation Example 1, except that PVPI was replaced by elemental iodine and PVP. The amount of elemental iodine was such that - and I3 - The total mass of the ions is 10% of the mass of the corresponding graftable polymer, and the amount of PVP used is the same as the amount of the PVP part in PVPI in Preparation Example 1.

[0093] Preparation Example 4

[0094] PGSPE was prepared by referring to the method in Preparation Example 3, except that the amount of elemental iodine was adjusted so that I in the stimuli-responsive pre-grafted solid polymer electrolyte - and I3 - The total amount of ions is 5% of the mass of the corresponding graftable polymer.

[0095] Preparation Example 5

[0096] PGSPE was prepared by referring to the method of the PEO-KFSI-PVPI solution in Preparation Example 1 (PVPI was 10 wt % of the mass of PEO), except that the amount of electrolyte salt was adjusted so that the molar ratio of polyethylene oxide to electrolyte salt was 15:1.

[0097] Comparative Example 1

[0098] PGSPE was prepared by referring to the method of the PEO-KFSI-PVPI solution in Preparation Example 1 (PVPI was 10 wt % of the mass of PEO), except that polyvinylpyrrolidone iodine was replaced by polyvinylpyrrolidone in the same amount.

[0099] Comparative Example 2

[0100] PGSPE was prepared by referring to the method of the PEO-KFSI-PVPI solution in Preparation Example 1 (PVPI was 10 wt% of the mass of PEO), except that the iodine element in the polyvinylpyrrolidone iodine was replaced by another element: S, and the amount used remained unchanged.

[0101] Test Case

[0102] The electrolytes obtained in the above-mentioned preparation examples 2-5 and comparative examples 1-2 were subjected to the same electrochemical performance test as the corresponding battery of the PGSPE (PVPI is 10wt% of the mass of PEO) in preparation example 1, and the results are shown in Table 2. Among them, the high voltage stability index refers to the charging cut-off voltage of the electrolyte used in the charge and discharge test in the potassium metal battery, the potassium metal stability index refers to the cycle time of the electrolyte used in the charge and discharge test in the potassium symmetric battery, and the charge and discharge stability index refers to the number of cycles obtained by using the electrolyte in the charge and discharge test in the potassium metal battery.

[0103] Table 2 (wherein Preparation Example 1 is the corresponding test data of PGSPE in which PVPI is 10wt% of the mass of PEO)

[0104]

[0105] It can be seen from Table 2 that, compared with the comparative example, the preparation example using the scheme of the present invention has an excellent all-solid-state battery with high voltage, high performance and stability, especially high electrochemical stability and high ionic conductivity.

[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A stimulus-responsive pre-grafted solid polymer electrolyte, characterized in that: The stimuli-responsive pre-grafted solid polymer electrolyte is prepared by mixing an iodine-containing graftable polymer or a raw material selected from an iodine compound and a graftable polymer, polyethylene oxide and an electrolyte salt, wherein the corresponding graftable polymer is at least partially grafted with the polyethylene oxide after the mixing process; the mass of the corresponding graftable polymer is 5%-20% of the mass of the polyethylene oxide, and the stimuli-responsive pre-grafted solid polymer electrolyte is rich in I - and I3 - ions, and I - and I3 - The total amount of ions is 2% to 10% of the mass of the corresponding graftable polymer.

2. The stimulus-responsive pre-grafted solid polymer electrolyte according to claim 1, characterized in that: The iodine-containing graftable polymer is selected from polyvinylpyrrolidone-iodine.

3. The stimulus-responsive pre-grafted solid polymer electrolyte according to claim 1, characterized in that: The iodine compound is selected from at least one of elemental iodine, potassium bismuth iodide, sodium triiodide, thallium triiodide, ammonium triiodide, nitrogen triiodide, phosphorus triiodide, antimony triiodide and gallium triiodide, and the graftable polymer is selected from at least one of polyvinyl pyrrolidone, polystyrene, polymethacrylate, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, and poly(vinylidene fluoride-co-hexafluoropropylene).

4. The stimulus-responsive pre-grafted solid polymer electrolyte according to claim 1, characterized in that: The molar ratio of polyethylene oxide to electrolyte salt is 5-20:

1.

5. The stimulus-responsive pre-grafted solid polymer electrolyte according to any one of claims 1 to 4, characterized in that: When the stimulus-responsive pre-grafted solid polymer electrolyte is stimulated by a voltage greater than 3V, a phase change occurs to generate a solid permeation phase.

6. The stimulus-responsive pre-grafted solid polymer electrolyte according to claim 1, characterized in that: The mixing process includes: dissolving each material in an organic solvent, stirring at 50-60° C. for 10-12 hours; then casting and forming, drying, and finally evaporating to remove the residual organic solvent.

7. The stimulus-responsive pre-grafted solid polymer electrolyte according to claim 6, characterized in that: The drying is natural drying in a low dew point environment of 30-50° C.; and / or, the evaporation conditions include: in a vacuum environment, a treatment temperature of 30-50° C., and a treatment time of 12-24 hours.

8. An all-solid-state battery, comprising a positive electrode and a negative electrode, characterized in that: It also includes a stimulus-responsive pre-grafted solid polymer electrolyte as described in any one of claims 1 to 7 disposed between the positive electrode and the negative electrode.

9. The all-solid-state battery according to claim 8, characterized in that: During the charging and discharging process of the all-solid-state battery, the stimulus-responsive pre-grafted solid polymer electrolyte undergoes a phase change to produce a solid permeation phase, resulting in direct contact between the solid permeation phase and the adjacent electrode, forming a void-free interface.

10. The all-solid-state battery according to claim 8, characterized in that: The area of ​​the stimulus-responsive pre-grafted solid polymer electrolyte is larger than the positive electrode area and larger than the negative electrode area; and / or, the area of ​​the stimulus-responsive pre-grafted solid polymer electrolyte is 1.2 to 1.5 times the area of ​​the positive electrode or the negative electrode.

11. The all-solid-state battery according to claim 8, characterized in that: The thickness of the stimuli-responsive pre-grafted solid polymer electrolyte is controlled at 100 μm-200 μm, and the positive electrode loading is 1.2-1.5 mg / cm 2 When the negative electrode is a metal negative electrode, the thickness of the metal negative electrode is 200-300 μm, and when the negative electrode is a graphite negative electrode, the loading amount of the graphite negative electrode is 1.5-2 mg / cm 2 .

12. The all-solid-state battery according to claim 8, characterized in that: The all-solid-state battery includes any one of an all-solid-state ion battery and an all-solid-state metal battery. The all-solid-state ion battery includes at least one of a lithium ion battery, a sodium ion battery, and a potassium ion battery. The all-solid-state metal battery includes at least one of a lithium metal battery, a sodium metal battery, and a potassium metal battery.